VD_FINDINFO Arrêt / 2025 / 783 vom 11. November 2025 - VD Tribunal cantonal (2025)
MÉTHODE MIXTE D'ÉVALUATION, REFUS DE LA PRESTATION D'ASSURANCE | 28 LAI, 28a LAI, 16 LPGA, 8 LPGA, 27 RAI, 27bis RAI, 69 al. 2 RAI